Normal concentrations of chromium in serum and urine–a TRACY project. - Brune, D.; Aitio, Antero; Nordberg, G.; Vesteberg, O.; Gerhardsson, Lars (Scandinavian Journal of Work, Environment & Health, 1993)
The validity of ``normal'' concentrations for total chromium in serum and urine (S-Cr and U-Cr, respectively) in papers published mainly in the last decade were evaluated and graded by two investigators according to TRACY criteria. The results were in close agreement. Because of possible contamination during sampling from stainless steel needles, the description of the sample collection method was considered important. Documentation of analytical quality control was emphasized. The chromium concentrations were categorized according to nonoccupational conditions that could influence the levels. Eighty-seven publications reporting chromium concentrations in blood and 58 on U-Cr were evaluated, 53 dealing with S-Cr and 41 with U-Cr being found suitable for the TRACY project. In selected publications the arithmetic mean values presented for S-Cr and U-Cr in individuals with no known exposure were within the following ranges: 1-3 nmol.1-1 for S-Cr and 2-10 nmol.1-1 or 0.2-1 mumol.mol creatinine-1 for U-Cr.